2006
DOI: 10.1152/jn.00327.2006
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Pair Specific Distribution and Grip-Type Modulation of Neural Common Input to Extrinsic Digit Flexors

Abstract: . Musclepair specific distribution and grip-type modulation of neural common input to extrinsic digit flexors. J Neurophysiol 96: 1258 -1266, 2006. First published May 24, 2006 doi:10.1152/jn.00327.2006. To gain insight into the synergistic control of hand muscles, we have recently quantified the strength of correlated neural activity across motor units from extrinsic digit flexors during a five-digit object-hold task. We found stronger synchrony and coherence across motor units from thumb and index finger fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
(57 reference statements)
4
24
0
Order By: Relevance
“…It has been demonstrated that interactions exist and that coactivations and motor unit synchronizations occur between the muscles of the thumb and those of the fingers during multidigit grasping tasks (Fuglevand 2011;Hockensmith et al 2005;Johnston et al 2005;Gandevia 1993, 1994;Winges et al 2006). If these muscles were used to control an artificial hand, the coordinated activities of both sets of muscles would cause simultaneous motions of the thumb and fingers.…”
Section: Muscle Coactivity Not Muscle Cross Talk Was Determinedmentioning
confidence: 99%
“…It has been demonstrated that interactions exist and that coactivations and motor unit synchronizations occur between the muscles of the thumb and those of the fingers during multidigit grasping tasks (Fuglevand 2011;Hockensmith et al 2005;Johnston et al 2005;Gandevia 1993, 1994;Winges et al 2006). If these muscles were used to control an artificial hand, the coordinated activities of both sets of muscles would cause simultaneous motions of the thumb and fingers.…”
Section: Muscle Coactivity Not Muscle Cross Talk Was Determinedmentioning
confidence: 99%
“…The intrinsic muscles recorded from were the First Dorsal Interosseous (FDI) and First Palmar Interosseous (FPI). A detailed description of wire electrode preparation, insertion, and verification of electrode placement in the target muscles is presented elsewhere ([13,25,26]). After the experimental session, we recorded EMG during isometric maximum voluntary contraction (MVC) of each muscle.…”
mentioning
confidence: 99%
“…For each trial, the average EMG amplitude of each muscle was expressed as a percentage of its MVC (%EMG). For analysis of the coordination of multi-muscle EMG activity we constructed an n-dimensional vector (n = 5 muscles) defined by the %EMG amplitude of each muscle (termed muscle activation pattern [25]; MAP). A unit MAP vector was computed for each trial and then averaged across trials within subject, wrist angles and conditions [4,20,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dozens of reports have since adopted this notion, including the following, among others: 1) within the same muscle (Garland and Miles 1997;Kamen and Roy 2000;Keen et al 2012;Laine and Bailey 2011;Mellor and Hodges 2005;Nordstrom et al 1990;Schmied et al 1993); 2) across synergistic muscles (Barry et al 2009;Bremner et al 1991a, b;Carr et al 1994;Gibbs et al 1997;Keen and Fuglevand 2004;McIsaac and Fuglevand 2007;Powers et al 1989;Winges and Santello 2004); 3) during tremor (Halliday et al 1999;Logigian et al 1988;Semmler and Nordstrom 1995); 4) in various neuromuscular pathologies (Baker et al 1992;Farmer et al 1990Farmer et al , 1993Kirkwood et al 1984;Mottram et al 2010;Schmied et al 1999); 5) during various muscle contraction paradigms, such as precision grip tasks (Hockensmith et al 2005;Huesler et al 2000;Kilner et al 2002;Santello and Fuglevand 2004;Winges et al 2006); 6) in exercise training (Boonstra et al 2009;Dartnall et al 2008Dartnall et al , 2011Griffin et al 2009;Mochizuki et al 2005;Schmied and Descarreaux 2010); and 7) during muscle fatigue (Boonstra et al 2008;Grönlund et al 2009;…”
mentioning
confidence: 99%